Oral Inflammation and The Role of Cytokine - Nuroh Najmi; Faisal Kuswandani; Anggun Rafisa; Felisha Febriane Balafif (Sean Institute, 2023)
Acute inflammation becomes chronic when inflammation prolongs. Oral inflammation can develop become chronic and can be serious disease. Cytokines are small secreted proteins released by cells have a specific effect on the interactions and communications between cells. Based on studied that cytokine can be one of markers of inflammation. In many diseases cytokines can be biomarkers of inflammation and recently many studies use cytokines as one of the biomarkers in additional examination for their studies